2021
DOI: 10.25302/01.2021.cer.140922827
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Chemotherapy Recovery at Home versus in the Hospital for Children with Acute Myeloid Leukemia

Abstract: What was the research about?Acute myeloid leukemia, or AML, is a type of blood cancer. Although 20 percent of children with leukemia have AML, AML causes more than half of all deaths from leukemia in children. Doctors use multiple courses of chemotherapy to treat AML. After each course, children with AML are at high risk for life-threatening infections. These infections can also delay the next course of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A survey of family support structures was added to prospective assessments part way through the prospective cohort study in response to themes identified in semi‐structured interviews with patients and caregivers. 22 , 23 Thus, information on support structures was available for a subset of families. As support structures may influence HRQOL, a post hoc assessment of support structures by income categories was performed (Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A survey of family support structures was added to prospective assessments part way through the prospective cohort study in response to themes identified in semi‐structured interviews with patients and caregivers. 22 , 23 Thus, information on support structures was available for a subset of families. As support structures may influence HRQOL, a post hoc assessment of support structures by income categories was performed (Table S1 ).…”
Section: Methodsmentioning
confidence: 99%